Coordinate Systems used in Satellite Technology - Bozorov, Maxmud Muminovich; Bozorov, Malik Muminovich; Fayziev, SHoxrux SHamsi o’g’li. (International Journal on Orange Technologies, 2022)
Quantities and participants in the optimal efficiency of the transfer from the coordinate transmission to the global satellite system (GSYT) from stable satellite technologies.